Making World Wide Web caching servers cooperate - Malpani, Radhika; Lorch, Jay; Berger, David (Proceedings of the Fourth International World Wide Web Conference, 1995)
Due to its exponential growth, the World Wide Web is increasingly experiencing several problems, such as hot spots, increased network bandwidth usage, and excessive document retrieval latency. The standard solution to these problems is to use a caching proxy. However, a single caching proxy is a bottleneck: there is a limit to the number of clients that can use the same cache, and thereby the effectiveness of the cache is limited. Also, a caching proxy is a single point of failure. We address these problems by creating a protocol that allows multiple caching proxies to cooperate and share their caches, thus increasing robustness and scalability. This scalability, in turn, gives each client an effectively larger cache with a higher hit rate. This paper describes a prototype implementation of this protocol that uses IP multicast to communicate between the servers.